2010
DOI: 10.1007/dcr.0b013e3181bc01d1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Age Distribution of Patients With Colorectal Cancer: Are the United States Preventative Services Task Force Guidelines for Colorectal Cancer Screening Appropriate?

Abstract: There has been a significant increase in the percentage of colorectal cancer patients older than age 75 years. Failing to screen patients younger than 50 years and older than the age of 75 years would miss 49% of patients treated at our institution from 2003 to 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
0
15
0
3
Order By: Relevance
“…We grouped 70-75 year olds together because previous research suggests that for individuals in this age range with a high burden of comorbidity life expectancy is similar and is less than the 10 years needed for benefit from screening. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] We carried out multivariable log binomial regression to identify independent predictors of screening utilization within 24 months of the qualifying 2010 visit and to calculate adjusted screening rates. Robust standard errors were used to adjust for clustering within facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We grouped 70-75 year olds together because previous research suggests that for individuals in this age range with a high burden of comorbidity life expectancy is similar and is less than the 10 years needed for benefit from screening. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] We carried out multivariable log binomial regression to identify independent predictors of screening utilization within 24 months of the qualifying 2010 visit and to calculate adjusted screening rates. Robust standard errors were used to adjust for clustering within facility.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients are unlikely to benefit from (and might even be harmed by) screening. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
Section: Outcome and Predictor Variablesmentioning
confidence: 99%
“…What happens to the population outside the screening age group? In an important study, Shellnut et al (2010) looked at the appropriateness of restricting the screened age group and found that not screening individuals under 50 and over 75 years would miss around 49 to 50% of patients in their study. Harmston et al (2010) looked at 100 patients with CRC in the NHSBCSP and analysed their symptoms.…”
Section: Who Screening Principlesmentioning
confidence: 99%
“…Incidence and death rates for colorectal cancer increases with age. In fact, 90% of new cases and 94% of deaths occur in individuals 50 years and older [4].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence and death rates for colorectal cancer increases with age. In fact, 90% of new cases and 94% of deaths occur in individuals 50 years and older [4].Overall, colorectal cancer incidence and mortality rates are approximately 35-40% higher in men than in women. The reasons for this are not completely understood, but they most likely stem For reprint orders, please contact: reprints@futuremedicine.com…”
mentioning
confidence: 98%